PENERAPAN MODEL PROBLEM-BASED LEARNING (PBL) DALAM PEMBELAJARAN PAI UNTUK MENGEMBANGKAN KETERAMPILAN BERPIKIR KRITIS - Musyafa, Wildayah; Khotimah, Siti; Syafe'i, Imam; Fauzan, Ahmad; Sunarto, Sunarto (STKIP Persada Khatulistiwa Sintang, 2026)
This study aimed to examine how the Problem-Based Learning (PBL) model is implemented in Islamic Education (PAI) and how it impacts the development of students’ critical thinking skills. The study employed a qualitative approach by analyzing various scientific literature, including journal articles, books, and relevant policy documents. To ensure the validity of the findings, data were analyzed using content analysis techniques involving data reduction, data display, and conclusion drawing. Source triangulation was also applied to strengthen the credibility of the results. The findings indicate that PBL enhances students’ ability to analyze information, evaluate arguments, draw rational conclusions, and make decisions. It also increases student engagement, motivation, and learning autonomy. Furthermore, the implementation of PBL not only improves students’ theoretical understanding of Islamic values but also equips them with critical thinking skills applicable to everyday life. In conclusion, this study provides a conceptual foundation for PAI teachers to design more active, collaborative, and creative learning strategies.